The relation between Mishna and Tosefta Rosh-Hashana - Barzel, Jacob (Department of Religious Studies, 2023)
In the following paper a comparison between the Mishnah and the Tosefta of Rosh Ha-Shanah is presented. Many theories have been put forward and much valuable material collected to explain the nature of the Tosefta. Nevertheless there are many points upon which no agreement has been reached and which require clarification and further discussion, such as: the sequence of the halakhoth in the Tosefta as compared with those of the Hishnah; does the Tosefta comprise elements differing in character and origin from those of the Hishnah? is the Tosefta an indenendent work naraleling the Mishnah or not effort is made in this work to answer these questions by annroaching the subject from a different angle, and by giving examples taken from Rosh Ha-Shanah. It is ,ronosed to show that the Tosefta is the first Talmud of the Mishnah . For this reason, the Tosefta is found to propound explanations of, and to contain quotations from. the Hishnah , in the same manner as does the Talmud. The Tosefta adds to the Mishnah: laws, opinions not in the Hishnah, Tannai tic conclusions in opposition to the 1V:ishnah, and the names of tannaim not mentioned in the Hishnah. Moreover, like the Mishnah, the Tosefta consists of different strata some of which were added after the completion of the Mishnah . The sequence of the Tosefta follows that of the Mishnah which preceded it. Reasons are given in the chapter, 11The Sequence in Hishnah and Toseftatt, for any divergencies from the sequence. The work of necessity deals with: Who com-oiled the Tosefta; when was it com-oiled ; the attitude of the Talmudim and ,4moraim to it; the relationship between Tosefta and Beraita; the character of the Tosefta as described by scholars.